INFLUENCE OF TRIMETAZIDINE ON SILENT MYOCARDIAL ISCHEMIA AND HEART RATE VARIABILITY AT THE PATIENTS RECEIVING ANTHRACYCLINE ANTIBIOTICS - Vatutin, N.Т.; Kalinkina, N.V.; Ridzhok, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The anthracycline antibiotics have cardiotoxic action. The purpose of this research is the study of influence trimetasidine on silent myocardial ischemia and heart rate variability (HRV) at the patients receiving anthracyclines. Material and methods: the daily monitoring of ECG with an estimation of heart rate, changes of ST segment and parameters of HRV is executed on 43 patients who received anthracyclines. The patients were divided into two groups: 1st group – 22 patients who received trimetazidine 3 times per day - 60 mg during 3 months, 2nd group – 21 patients without therapy of cardioprotection. The patients were examined twice: before the beginning of therapy with trimetazidine and 3 months later. The mean cumulative dose of anthracycline at the 1st examination – 765,4±209,1 mg/m2, at the 2nd – 1165,1±114,2 mg/m2. Results show that the anthracyclines cause the development of silent myocardial ischemia, decrease of HRV, activation of sympathetic and depression of parasympathetic nervous system. Trimetasidine therapy leads to decrease of intensity of silent ischemia, increase of HRV, decrease tone of sympathetic and increase tone of parasympathetic nervous system. Intensity of silent ischemia and disturbance of HRV were increased at the patients without therapy of cardioprotection as the doze of anthracycline was raised to more than 1000 mg/m2.